The Effect of Integrated Instagram and Tiktok Learning Media With PBL Learning Model on Increasing Student Learning Outcomes on The Topic of Qualitative Analysis of Cation - Hayuni Retno Widarti; Deni Ainur Rokhim; Munzil Munzil; Neena Zakia (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Information and communication technology development demands a transformation of education, especially in fulfilling innovation in learning media. Learning media is an urgent means of teaching and learning chemistry. Students' skills can be developed by increasing motivation and collaboration through digital technology. This research aims to determine the effect of the integrated Instagram (IG) and TikTok with the PBL learning model on student learning outcomes in qualitative analysis courses. The research method used was a quasi-experimental research design with a Pretest-Posttest Control Group design. The sample used came from a 2nd-year undergraduate student, Department of Chemistry, the State University of Malang, which consisted of 4 classes, two control classes with 44 students and two experimental classes with 50 students. Data analysis used preliminary tests and hypothesis testing. The preliminary test of the research data showed that the data were not normally distributed, so the hypothesis test used the Mann-Whitney test. The results of the hypothesis test show the Asymp value. Sig. (2-tailed) of 0.021 (0.021<0.05), it can be concluded that the use of integrated IG and TikTok learning media with the PBL learning model can increase student learning outcomes of 2nd-year undergraduate students on qualitative analysis of cation